Subgroup Analysis Comparing Ultrathin, Bioresorbable Polymer Sirolimus-Eluting Stents Versus Thin, Durable Polymer Everolimus-Eluting Stents in Acute Coronary Syndrome Patients - Roguin, Ariel; Kandzari, David E; Marcusohn, Erez; Koolen, Jacques J; Doros, Gheorghe; Massaro, Joseph M; Garcia-Garcia, Hector M; Bennett, Johan; Gharib, Elie G; Cutlip, Donald E; Waksman, Ron (Circulation. Cardiovascular interventions, 2018)
Presentation with acute coronary syndromes (ACS) constitutes a high-risk subset of patients with worse outcome after percutaneous coronary intervention. We report clinical outcomes in subjects with ACS from the BIOFLOW V trial (BIOTRONIK - A Prospective Randomized Multicenter Study to Assess the Safety and Effectiveness of the Orsiro Sirolimus Eluting Coronary Stent System in the Treatment of Subjects With up to Three De Novo or Restenotic Coronary Artery Lesions) comparing an ultrathin strut (60 μm) bioresorbable polymer sirolimus-eluting stent (BP-SES) with a thin strut (81 μm) durable polymer everolimus-eluting stent (DP-EES). Among 1334 patients randomized to 2:1 treatment with either BP-SES or DP-EES, 677 (50.7%) ACS patients without ST-segment-elevation myocardial infarction (MI; 454 BP-SES and 223 DP-EES) were identified in the retrospective post hoc analysis. The primary end point of 12-month target lesion failure, individual component end points, and stent thrombosis were evaluated. Recurrent MI was defined as a ≥50% increase of creatine kinase-myocardial band or in the absence of creatine kinase-myocardial band, troponin >50% increase over previous level and >3× the upper limit of normal). All events were adjudicated by a blinded independent clinical events committee. Overall, baseline clinical, angiographic, and procedural characteristics of the ACS population were similar between the 2 treatment groups. At 12 months, target lesion failure occurred in 5.6% (24/426) of BP-SES patients versus 11.0% (23/209) in DP-EES patients ( P=0.02); target lesion failure composite components were cardiac death, 0% versus 1.0% ( P=0.11); target vessel-related MI, 3.5% versus 9.7% ( P=0.003); and clinically driven target lesion revascularization, 2.8% versus 3.4% ( P=0.80). Spontaneous target vessel MI was 0.5% (2/425) for BP-SES versus 2.4% (5/206) for DP-EES ( P=0.041). Stent thrombosis rates at 1 year were similar (0.5% versus 1.0%; P=0.601). In the ACS subgroup population of the BIOFLOW V study, treatment with BP-SES compared with DP-EES was associated with a significantly lower rate of 12-month target lesion failure, a difference driven by significantly lower periprocedural MI and spontaneous MI. These findings support treatment with an ultrathin strut BP-SES in ACS patients undergoing percutaneous coronary intervention. URL: https://www.clinicaltrials.gov . Unique identifier: NCT02389946.